Heat treatment effects on microstructure and properties of CVI SiC/SiC composites with Sylramic™-iBN SiC fibers. Issue 6 (June 2023) - Bhatt, R.T.; Eldridge, J.I.
Abstract: Chemical-vapor-infiltrated (CVI) SiC/SiC composites with Sylramic™-iBN SiC fibers and CVI carbon, BN, and a combination of BN/C interface coating were heat treated in 0.1-MPa argon or 6.9-MPa N2 at temperatures to 1800 °C for exposure times up to 100 hr. The effects of thermal treatment on constituent microstructures, in-plane tensile properties, in-plane and through-the-thickness thermal conductivities, and creep behavior of the composites were investigated. Results indicate that heat treatment affected stoichiometry of the CVI SiC matrix and interface coating microstructure, depending on the interface coating composition and heat treatment conditions. Heat treatment of the composites with CVI BN interface in argon caused some degradation of in-plane properties due to the decrease in interface shear strength, but it improved creep resistance significantly. In-plane tensile property loss in the composites can be avoided by modifying the interface composition and heat treatment conditions.